2016
DOI: 10.5603/arm.2016.0042
|View full text |Cite
|
Sign up to set email alerts
|

A Clinic-Epidemiological Study of Head and Neck Tuberculosis—A Single-Center Experience

Abstract: The number of patients diagnosed in our center declined in the first period of 12 years and remained stable over the last 24 years, as were the common sites of head and neck EPTB (larynx and cervical lymph nodes). In patients with head and neck TB the biopsy specimens should be examined not only histologically but also for the presence of Mycobacterium tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In fact, more than 62.9% of laryngeal TB patients were reported before the year 2007. In the study by Pajor, which included patients from 1978 to 2013, the larynx was also found to be the most common site of HNTB 18 . Therefore, studies only including patients in the most recent ten years may reach a different conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, more than 62.9% of laryngeal TB patients were reported before the year 2007. In the study by Pajor, which included patients from 1978 to 2013, the larynx was also found to be the most common site of HNTB 18 . Therefore, studies only including patients in the most recent ten years may reach a different conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Because the early manifestation of HNTB is often similar to neoplasms or inflammation and because the systemic symptoms of tuberculosis may not be obvious, clinical consideration of HNTB usually occurs only after an ineffective anti-inflammatory treatment, biopsy, or even surgical resection 2 , 12 16 . Despite the large number of existing reports, the patient risk of medical injury and occupational exposure caused by a delayed diagnosis of HNTB does not seem to have decreased over the past decade 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Because manifestations of TB in the head and neck are clinically similar to inflammation or neoplasms, and because of its rarity in low prevalence regions, clinical consideration of TB as a differential diagnosis often occurs quite lately 14,15 and has not decreased in the past few decades 16 . In this regard, an origin in a region with high prevalence of TB in the population or family members with a known or suspected history of TB can lead to an earlier diagnostic suspicion 4 .…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of recent case series of extrapulmonary TB from low-risk countries, although these are not directly applicable to the UK population. [11][12][13][14][15] In 2006, Menon et al published a series of 128 patients with head and neck TB in Bradford, which had a relatively high incidence of TB compared with the UK average. 16 This series confirmed lymph node predominant disease but also demonstrated the diverse ways in which TB can present in the head and neck.…”
Section: Introductionmentioning
confidence: 99%